Making Corporate Social Responsibility Operable - Frere, Claudia (2007)
This research project investigates the nature of making CSR operable within the financial services industry. It reviews the external context in which firms engage in CSR, their response and how these factors influence internal CSR management and operations. Drawing from a multi-perspective discipline, the research incorporates CSR concepts and theoretical implications from market and non-market motivations and strategic management perspectives of network and institutional theories. Concepts of CSR management are further added to provide context for the research scope. The research involves interviewing firms in the financial services industries who have formalized CSR policies and related business services. The report seeks to understand the effectiveness and performance of CSR policies through assessment and analysis of how CSR is made operable within the firm.